Interleukin-18 Mediates Immune Responses to Campylobacter jejuni Infection in Gnotobiotic Mice. - Stefan Bereswill; Marie E Alutis; Ursula Grundmann; André Fischer; Ulf B Göbel; Markus M Heimesaat (PLoS ONE, 2016)
BACKGROUND:Human Campylobacter jejuni infections are progressively rising worldwide. Information about the molecular mechanisms underlying campylobacteriosis, however, are limited. In the present study we investigated whether cytokines such as IL-23, IL-22 and IL-18, which share pivotal functions in host immunity, were involved in mediating intestinal and systemic immunopathological responses upon C. jejuni infection. METHODOLOGY/PRINCIPAL FINDINGS:To assure stable infection, gnotobiotic (i.e. secondary abiotic) IL-23p19-/-, IL-22-/- and IL-18-/- mice were generated by broad-spectrum antibiotic treatment. Following peroral C. jejuni strain 81-176 infection, mice of all genotypes harbored comparably high pathogenic loads in their intestines. As compared to wildtype controls, however, IL-18-/- mice displayed less distinct C. jejuni induced sequelae as indicated by less pronounced large intestinal shrinkage and lower numbers of apoptotic cells in the colonic epithelial layer at day 8 postinfection (p.i.). Furthermore, lower colonic numbers of adaptive immune cells including regulatory T cells and B lymphocytes were accompanied by less distinct secretion of pro-inflammatory cytokines such as TNF and IFN-γ and lower IL-17A mRNA expression levels in colonic ex vivo biopsies of infected IL-18-/- as compared to wildtype mice. Upon C. jejuni infection, colonic IL-23p19 expression was up-regulated in IL-18-/- mice only, whereas IL-22 mRNA levels were lower in uninfected and infected IL-23p19-/- as well as infected IL-18-/- as compared to respective wildtype control mice. Remarkably, not only intestinal, but also systemic infection-induced immune responses were less pronounced in IL-18-/- mice as indicated by lower TNF, IFN-γ and IL-6 serum levels as compared to wildtype mice. CONCLUSION/SIGNIFICANCE:We here show for the first time that IL-18 is essentially involved in mediating C. jejuni infection in the gnotobiotic mouse model. Future studies need to further unravel the underlying regulatory mechanisms orchestrating pathogen-host interaction.